Recognition of delirium in ICU patients: a diagnostic study of the NEECHAM confusion scale in ICU patients - Schuurmans Marieke J; Immers Henny EM; van de Bijl Jaap J (BMC, 2005)
Abstract Background A delirium, is a serious, high-frequency complication in intensive care unit (ICU) patients. The consequences of this complication range from high morbidity and mortality to greater need for nursing care. Despite these, delirium is often not recognized and there for not treated. In this study a nursing screening instrument, the NEECHAM confusion scale, was studied for early recognition of delirium ICU patients. This scale proved valid and reliable in several studies in the general hospital population. Methods In this study validity and reliability were tested in a prospective cohort of 105 patients. Gold standard for delirium was an independent DSM-IV diagnosis. User friendliness was tested by structured evaluation of nurses' experiences working with the scale. Results The NEECHAM confusion scale showed high internal consistency (Cronbach's alpha 0.88) and an interrater reliability of Cohen's Kappa 0.60. The concurrent validity with the DSM-IVcriteria showed a strong link (chi-square 67.52, p [less than or equal to] 0.001). Sensitivity was high, 97% and specificity was good 83%. ICU nurses completed the NEECHAM confusion rating in 3.69, ± 1.21 minutes average. In general the nurses were positive about the NEECHAM confusion scale. They were able to collect data during regular care, but experienced problems in rating the scale in intubated patients. The items in themselves were clear, the content validity, measured by the language used was rated good. Conclusion The psychometric characteristics of the NEECHAM confusion scale of this ICU study are generally consistent with validity research previously reported for the general hospital population. The psychometric characteristics and the ease of use of the NEECHAM confusion scale enables ICU nurses to early recognize delirium. Further study, especially in intubed patients is recommended.